Compact ADOV Routing and the Bat Algorithm for Advanced Route Optimization in MANET: Improving Trust Routes and Network Performance in MANET using EROiBA (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The MANET is described as a wireless dynamic topology network. It doesn't have a centralizedunit to control the other nodes and nodes are configured within the network.The trust route is verychallenging issues in the network. The available routes are not sure to complete this data transmissiontask perfectly due to the dynamic topology and less centralized configuration. This reduces networkperformance such as packet drop or incomplete data transmission. In this paper, the Enhanced Routeoptimization techniques are introduced with the support of the Bat Algorithm (EROiBA) in MANET. Thistechnique creates the trust and best route from source to destination. In fact, trust and the best routesare selected by the node iteration condition and the average total energy level of the nodes between thesources to destination. The iteration of the sender node is a detail of the previous performance ratio ofthe adjacent node evaluated by the source node. The EROiBAis simulated in ns-2 tools andobservesthisoutcome such as packet delivery ratio, end-to-end delay and throughput. The result of theEROiBA is improved over existing work.